Cryptogenic Invasive Klebsiella Pneumoniae Liver Abscess Syndrome: Case Report (Revista de Medicina Clinica, 2025)
The Cryptogenic Invasive Liver Abscess Syndrome is a complication of primary Klebsiella pneumoniae liver abscesses. Determined by septic metastatic dissemination to extrahepatic loci such as the lung, eye or CNS, it associates high morbidity but low mortality. Initially described in Taiwan in 1986, it is practically limited to Southeast Asia. However, recently it has been increasingly documented in non-Asian populations and in other global regions, with rising incidence. We hereby report the case of a young male without Asian ascendancy presenting with high fever, generalized myalgias, unspecified abdominal pain and total amaurosis of the left eye. Upon testing, a K. pneumoniae cryptogenic liver abscess is detected with associated pulmonary septic emboli, endogenous endophthalmitis and a gluteal abscess.
Keywords: Klebsiella pneumoniae; Pyogenic Liver Abscess; Lung Abscess; Endophthalmitis